2016
DOI: 10.5585/iji.v4i1.73
|View full text |Cite
|
Sign up to set email alerts
|

Organizational resilience: a comparative study between innovative and non-innovative companies based on the financial performance analysis

Abstract: Organizational resilience is defined as the ability and capacity of an organization to withstand unexpected changes, discontinuities and environmental risks. Innovation contributes to achieve resilience as it enables organizations to renew over time. Our aim in this article is to analyze the relationship between innovation and resilience from the financial performance analysis with EBITDA, ROE and ROA indicators. We investigated a total of 10 companies divided into two groups, where the first was a group of 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 30 publications
0
36
0
4
Order By: Relevance
“…Previous research agrees that financial resources can help to handle acute crises and recover from them (e.g., Burke 2005;de Carvalho et al 2016;Lampel et al 2014). Analyzing airline industry responses to September 2011, Gittell et al (2006) found that airlines with greater financial resources (low levels of debt and high levels of cash on hand) were able to retain staff (instead of laying off staff) and thus had more human resources to recover.…”
Section: Resource Availabilitymentioning
confidence: 95%
“…Previous research agrees that financial resources can help to handle acute crises and recover from them (e.g., Burke 2005;de Carvalho et al 2016;Lampel et al 2014). Analyzing airline industry responses to September 2011, Gittell et al (2006) found that airlines with greater financial resources (low levels of debt and high levels of cash on hand) were able to retain staff (instead of laying off staff) and thus had more human resources to recover.…”
Section: Resource Availabilitymentioning
confidence: 95%
“…Performance. Based on literature review (e.g., Dalziell & McManus, 2004 ; De Carvalho et al, 2016 ; Rodríguez-Sánchez, Guinot, Chiva, & López-Cabrales, 2019 ), this research evaluates hotel performance with both economic and intangible indicators. The developed scale includes five items such as return on investment, average sales growth, average market share growth, company image and reputation, and customer loyalty.…”
Section: Methodsmentioning
confidence: 99%
“…In this line, Chowdhury et al (2019) evidence an empirical association between adaptive resilience and business performance post-disaster, considering levels of debt, cash flow or profitability. Also, De Carvalho, Ribeiro, Cirani, and Cintra (2016) suggest that innovative companies are more resilient and better able to withstand crisis situations, in terms of financial performance measured by economic indicators such as return on asset and return on equity. Dalziell and McManus (2004) propose a holistic approach arguing that organisational resilience may be reaching stated objectives or mission statement areas, such as dividends for shareholders or reputation for quality products.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Hamel e Välikangas (2003) argumentaram que as organizações de sucesso são aquelas que entendem a natureza dinâmica de seus ambientes de negócios, dispostas a adaptarem-se às súbitas mudanças no ambiente. Carvalho et al (2016) propõem que é através da inovação que a organização será capaz de se renovar ao longo do tempo.…”
Section: Kotliarencounclassified